Ketaatan Kegiatan Usaha Skala Besar dan Menengah dalam Pengendalian Pencemaran Air di Kota Surabaya - Muhammad Rizky Firmansyah; Nurvita Cundaningsih (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
Due to continuous business expansion, Surabaya has serious environmental management problems. The purpose of this study is to evaluate how well business actors comply with the guidelines in the Environmental Management Efforts-Environmental Monitoring Efforts (UKL-UPL) and Environmental Impact Analysis (AMDAL) papers. Surveys, interviews and document analysis are some of the data collection methods used in this descriptive-comparative study design. According to the results of the study, the compliance of corporate activities increased in 2024, indicating that the monitoring efforts were successful. In order to improve corporate compliance with environmental management, this study suggests the expansion of monitoring capacity, training and the integration of information technology in monitoring. It is believed that these results would serve as a basis for more flexible and successful regulations to maintain the environmental quality of Surabaya.